No association between estrogen receptor gene polymorphisms and premature thelarche in girls. (3rd October 2017) - Lee, Hae Sang; Yoon, Jong Seo; So, Cheol Hwan; Kim, Kyung Hee; Hwang, Jin Soon
Abstract: Objective : Premature thelarche (PT) is a benign, nonprogressive condition defined as isolated breast development. While the pathophysiology of PT remains unclear, increased sensitivity to estrogen may cause PT. The aim of this study was to investigate the association between polymorphisms in the estrogen receptor alpha ( ERα) gene and PT in girls. Methods : In this case–control study, we examined 96 girls referred for early breast development (before the age of 8 years). The control group included healthy Korean females with normal pubertal progression. Anthropometric and hormonal parameters were measured and PvuII and XbaI ERα gene polymorphisms were evaluated by PCR. Out of the 96 girls, all coding exon and exon-intron boundaries of ERα were sequenced from the DNA of 46 girls. Results : There was no significant difference in the distribution of PvuII and XbaI polymorphisms between patients and controls. However, the carriers of XbaI polymorphisms had more advanced Tanner stage than did the non-carriers. Also, four ERα gene polymorphisms were previously identified, but these polymorphisms had no clinical significance. Conclusion : No association was found between the ERα gene polymorphisms and PT in girls. However, XbaI polymorphisms may contribute to early breast budding.